Feasibility study of using smart aggregates as embedded acoustic emission sensors for health monitoring of concrete structures. (18th October 2016) - Li, Weijie; Kong, Qingzhao; Ho, Siu Chun Michael; Lim, Ing; Mo, Y L; Song, Gangbing
Abstract: Acoustic emission (AE) is a nondestructive evaluation technique that is capable of monitoring the damage evolution of concrete structures in real time. Conventionally, AE sensors are surface mounted on the host structures,  however, the AE signals attenuate quickly due to the high attenuation properties of concrete structures. This study conducts a feasibility study of using smart aggregates (SAs), which are a type of embedded piezoceramic transducers, as embedded AE sensors for the health monitoring of concrete structures. A plain concrete beam with two surface mounted AE sensors and two embedded SAs was fabricated in laboratory and loaded under a designed three-point-bending test. The performance of embedded SAs were compared with the traditional surface mounted AE sensors in their ability to detect and evaluate the damage to the concrete structure. The results verified the feasibility of using smart aggregates as embedded AE sensors for monitoring structural damage in concrete. Potentially, the low cost smart aggregates could function as embedded AE sensors,  providing great sensitivity and high reliability in applications for the structural health monitoring of concrete structures.